Mengenal Dasar-Dasar Kewirausahaan dan Membangun Mindset Entrepneur - Akob, Muh; Tangngisalu, Jannati; Fajriah, Yana; Qiftih, Kurniah Mariatul; Mangerangi, Muhammad Nur Alamsyah; Halik, Syahrul (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
The introduction of entrepreneurship is believed to be able to change the conventional youth mindset into an entrepreneurial mindset so that the entrepreneurial mindset can grow starting from school. Therefore, there is a need for a facilitator to build an entrepreneurial mindset through training that will provide innovative thinking tendencies. Community Service Activities (PKM) aim to train the Young Generation gradually to have entrepreneurial and business competencies, Change the thought process and way of looking at the world that encourages entrepreneurial behavior for the Young Generation and Develop human resources that are able to create job opportunities for themselves and others according to the demands of Development. The implementation of this community service starts from the preparation, implementation and post-evaluation stages. The results of this PKM activity are about the application of Basic Entrepreneurship training and how to Build an Entrepreneurial Mindset to students who succeed in improving entrepreneurial skills so that they can build an entrepreneurial spirit.